Asalımsı idealler - Balkancı, Nagihan (My University, 2025)
Asalımsı idealler Asal idealler ve genelleştirmeleri, cebirsel yapıların karakterizasyonunda kullanılmasının yanı sıra Graf Teori, Genel Topoloji, Cebirsel Geometri, Şifreleme, Kodlama Teorisi gibi alanlara uygulamasının bulunması sebebiyle Değişmeli Cebirde çok önemli bir yere sahiptir. Örneğin, tamlık bölgeleri, cisimler, Noetherian halkalar, Prüfer Bölgeleri, TİB gibi birçok halka sınıfı asal idealler yardımıyla karakterize edilir. Sayılar teorisinde, aritmetiğin temel teoremi her tam sayının asal sayıların çarpımı şeklinde, ilgililik ve sıra düşünülmeksizin tek türlü biçimde yazılabileceğini söyler. Asal sayıların bu özelliği birçok cebirsel yapının temelini oluşturmakta, şifreleme gibi bilgi güvenliği alanlarında asal sayıların kullanılmasına olanak sağlamaktadır. Aritmetiğin temel teoremini Noetherian halkalara asalımsı idealler yardımıyla genişletebiliriz. Yalnızca bu açıdan bile bakıldığında asal ideallerin bir genişlemesi olan asalımsı ideallerin değişmeli halkalar teorisindeki önemi ortaya çıkar. R birimli ve değişmeli bir halka ve Q,R nin bir has ideali olsun. Her p,q∈R için pq∈Q iken p∈Q veya bir n∈N için q^n∈Q oluyorsa Q ya bir asalımsı ideal denir. Q bir asalımsı idealse √Q={x∈R: bir n≥1 tamsayısı için x^n∈Q}=P bir asal idealdir ve bu durumda Q ya bir P-asalımsı ideal denir. Noetherian halkalarda her ideal sonlu tane asalımsı idealin arakesiti olarak yazılabilir. Bu yazılışa asalımsı ayrışım denir. Z tamsayılar halkasındaki asalımsı ayrışım kullanılarak aritmetiğin temel teoremi elde edilir. Bu tez çalışmasında asalımsı ideallerin özel bir alt sınıfının cebirsel özellikleri incelenecektir. R nin Q idealine her I,J ideali için IJ⊆Q iken I⊆Q veya bir n∈N için J^n⊆Q oluyorsa potently asalımsı denir. Her potently asalımsı ideal bir asalımsı idealdir, fakat tersi doğru değildir. Bu çalışmada potently asalımsı ideallerle asalımsı, düzgün asalımsı, Noether kuvvetli asalımsı, Mori kuvvetli asalımsı idealler arasındaki ilişkiler incelenecektir.

Primary ideals Prime ideals and their generalizations have an important place in Commutative Algebra since not only are they used in the characterization of Algebraic Structures but also they have applications to other areas such as Graph Theory, General Topology, Algebraic Geometry, Cryptology, Coding Theory. For instance, Many classes of rings such as integral domains, fields, Noetherian rings, Prüfer domains, principal ideal domains are characterized in terms of prime ideals. In Number Theory, Fundemantal theorem of arithmetic states that every integer can be represented uniquely as a product of prime numbers, up to the order and associated elements. This propert of prime numbers forms the basis of many algebraic structures and enables the use of prime numbers in information security fields such as encryption. We extend the fundemantal theorem of arithmetic to Noetherian rings by means of primary ideals. From this point of view alone, the importance of the primary ideals, which is a generalization of prime ideals, in the theory of commutative rings arises. Let R be a commutative ring with a unity and Q be a proper ideal of R. Q is said to be a primary ideal if whenever ab∈Q for every a,b∈R then a∈Q or b^n∈Q for some integer n≥1. If Q is a primary ideal, then √Q={x∈R: ∃ n≥1 such that x^n∈Q}=P is a prime ideal of R, and in this case Q is said to be a P-primary ideal of R. In Noetherian rings, every ideal can be represented as a finite intersection of primary ideals. This representation is called primary decomposition. Fundemantal theorem of arithmetic can be obtain by using primary decomposition in the ring Z of integers. In this thesis, algebraic properties of a special sub-class of the primary ideals will be examined. A proper ideal Q of R is said to be a potently primary if whenever IJ⊆Q for every ideals I,J of R then I⊆Q or J^n⊆Q for some integer n≥1. Every potently primary ideal is also a primary ideal but the converse is not true in general. In this work, the relations between potently primary ideals and other classical ideals such as primary, uniformly primary, Noether and Mori strongly primary ideals will be investigated.
Primary ideals
Keywords: Asalımsı ideal; düzgün asalımsı ideal; Matematik; Mathematics; Mori kuvvetli asalımsı ideal; Mori strongly primary ideal; Noether kuvvetli asalımsı ideal; Noether strongly primary ideal; Öğrenim ve öğretim; potently asalımsı ideal Primary ideal; potently primary ideal; Study and teaching; uniformly primary ideal